2016
DOI: 10.17795/jjnpp-33613
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Evaluation of a Fast-Dissolving Drug Delivery System for Loratadine Using the Electrospinning Method

Abstract: Background: Due to their optimal mechanical and biological properties, nanofibers have numerous medical applications. Electrospinning is one of the widely used techniques for generating drug-containing nanofibers. Objectives: The aim of this study was to assess the use of the electrospinning method to prepare fast-dissolving loratadine nanofibers. Materials and Methods: Polyvinylpyrrolidone (PVP) nanofibers containing loratadine were produced using the electrospinning method. A full factorial design was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Erosion studies are important because, based on the desired application, films absorbing and maintaining their physical integrity are as useful as those that absorb solvents and then erode over time. The former properties are more suitable for filtration applications while the latter could have important pharmaceutical applications where they can be used for controlled release formulation of some highly soluble drugs …”
Section: Resultssupporting
confidence: 67%
“…Erosion studies are important because, based on the desired application, films absorbing and maintaining their physical integrity are as useful as those that absorb solvents and then erode over time. The former properties are more suitable for filtration applications while the latter could have important pharmaceutical applications where they can be used for controlled release formulation of some highly soluble drugs …”
Section: Resultssupporting
confidence: 67%
“…The formation of the gel layer not only hinders the release of the drug but also decreases the rate of erosion of the tablets. 30,31 When different statistical models were applied to the evaluation of the release pattern of the drug, it was found that formulations F1, F2, F3, F5, F6s and F8 followed the Higuchi model whereas F4 and F7 followed the Korsmeyer-Peppas model and F9 followed the zero-order kinetics model. The value of n showed that the release of the drug from formulations F1 to F8 followed Fick's diffusion (case 1 transport/ anomalous transport) as the value of n < 0.49 and F9 followed non-Fickian.…”
Section: Discussionmentioning
confidence: 99%
“…Erosion studies are important because, based on the desired application, films absorbing and maintaining their physical integrity are as useful as those that absorb solvents and then erode over time. The former properties are more suitable for filtration applications while the latter could have important pharmaceutical applications where they can be used for controlled release formulation of some highly soluble drugs …”
Section: Resultsmentioning
confidence: 99%